Інформаційне забезпечення Національної поліції України - Калєніченко, Л. І.; Kalienichenko, L. I.; Калєніченко Лідія Іванівна (Безпека у кіберсфері : зб. матеріалів Міжнар. наук.-практ. конф. (м. Кам’янець-Подільський, 28 трав. 2025 р.). – Кам’янець-Подільський: ХНУВС, 2025. – С. 146-147, 2025)
Зазначено, що Єдина інформаційна система МВС є інтегрованою інформаційною системою, що безпосередньо забезпечує реалізацію функцій її суб’єктів, інформаційну підтримку та супроводження їх діяльності і становить сукупність взаємозв’язаних функціональних підсистем. Використання інформаційних ресурсів ЄІС МВС працівниками поліції в цілому чітко регламентується законодавством України. Створення та використання власних інформаційно-пошукових систем Національною поліцією України координується МВС України, регулюється нормами законодавства та обмежено площиною функцій і завдань, які покладено державою і суспільством на поліцію.

It is noted that the Unified Information System of the Ministry of Internal Affairs is an integrated information system that directly ensures the implementation of the functions of its subjects, information support and monitoring of their activities and constitutes a set of interconnected functional subsystems. The use of information resources of the Unified Information System of the Ministry of Internal Affairs by police officers is generally clearly regulated by the legislation of Ukraine. The creation and use of its own information and search systems by the National Police of Ukraine is coordinated by the Ministry of Internal Affairs of Ukraine, regulated by legislative norms and limited by the scope of functions and tasks assigned to the police by the state and society.
Keywords: Національна поліція України; інформаційне забезпечення; Єдина інформаційна система МВС; ЄІС МВС; "Інформаційний портал Національної поліції України"; National Police of Ukraine; information support; Unified Information System of the Ministry of Internal Affairs; "Information Portal of the National Police of Ukraine"